Pengaruh Art Therapy (TERAPI Menggambar) Terhadap Stres Pada Lansia - Dewa Agus Gede Agung Agus Setiana; Cristin Wiyani; Rizky Erwanto (Universitas Aisyiyah Yogyakarta, 2017)
The objective of research to identify the effects of art therapy on stress in elderly at BPSTW Yogyakarta Unit Budi Luhur. This method of research employed quantitative type of quasi experiment with pre test and post test method nonequivalent control group. The sampel size of 36 responden. Measurement of stress levels using DASS 42. The research conducted for 8 days. The first day of measure pre test, and second day art therapy began until day 8, and post test measure after art therapy was given on the last day. The effect of art therapy on stress of elderly was analyzed bivariate using t test paired t test independent. The result using t test-paired in the intervention group indicated p value = 0,000 (p value0,05), and the control group indicated p value 0,067 (p value0,05). The result using t test-independent in post test of both groups in indicated p value = 0,000 (p value0,05). Conclusion there is influence art therapy (drawing therapy) to stress at elderly in BPSTW Yogyakarta Unit Budi Luhur.